Towards a strategy for the recovering of the Mediterranean monk seal in the Adriatic-Ionian Basin - Panou, Aliki; Giannoulaki, Marianna; Varda, Dušan; Lazaj, Lorela; Pojana, Giulio; Bundone, Luigi (Frontiers in Marine Science, 2023)
Occasional but recurrent sightings indicate that the endangered Mediterranean monk seal is still present in most of its historical range within the Adriatic-Ionian region in the central Mediterranean Sea. However, in most of the adjacent countries, the species’ abundance and distribution are practically unknown. An actively reproducing sub-population with a minimum of 22 adult/sub-adult seals lives in the Greek central Ionian Sea. The latter can form a nucleus from which the entire Adriatic-Ionian Basin could be re-colonized if adequate conservation measures are implemented throughout the area and in a coordinated manner. We examine the historical presence in the region as a baseline for providing a benchmark for conservation. We further examine the habitat availability for the species taking into consideration the existing Marine Protected Areas (MPAs) and other relevant parameters crucial for its conservation (e.g. possibilities for rapid assessment, spatial aspects including corridors for connectivity purposes, needs for public awareness, etc.). We recommend a series of interlinked actions within the framework of a conservation strategy the implementation of which will ensure the conditions for maintaining ecologically, demographically, and genetically viable sub-populations of this species emblematic for the entire Mediterranean Sea. To achieve this goal, a coalition of partners from this area is required in order to adopt the strategy and jointly implement the measures required.